THE COMPETENCY MAPPING ANALYSIS OF INVESTIGATOR EMPLOYEE IN THE REPRESENTATIVE OFFICE OF NATIONAL POPULATION AND FAMILY PLAN AGENCY OF EAST JAVA PROVINCE - Nur Hotimah (Airlangga Development Journal, 2023)
Problems in an organization in the Government sector, especially in Family Planning Extension Officers at the Representative Office of the National Population and Family Planning Agency of East Java Province among others is the accumulation of employees in one unit without a clear job and the lack of employees in other units is the reality of the problem. On the other hand, the formation of organizational work programs tends not to be based on real needs, in the sense that the organizations formed are too large while the workload is so large and feels heavy, so that the achievement of organizational goals is not efficient and effective because of the incompatibility of competencies possessed between one employee and another. The purpose of the study was to find out and analyze the competency mapping of KB extension workers at the Representative Office of the National Population and Family Planning Board of East Java Province. This study uses a qualitative approach with a descriptive method. The results of this study conclude that the competence of KB KB Extension Officers is a combination of skills, knowledge, and attitudes that can be linked to performance in a causal flow model which shows that goals, temperament, self-concept, and work personality which then predict competency performance include intentions. , actions and final results, to the application of 5 (five) types of competency characteristics, namely motives (consistent will as well as the cause of action), innate factors (consistent character and response), self-concept (self-image), knowledge (information in the field of certain) and skills (the ability to perform tasks).